2012
DOI: 10.1039/c2cs35200a
|View full text |Cite
|
Sign up to set email alerts
|

Ice nucleation by particles immersed in supercooled cloud droplets

Abstract: The formation of ice particles in the Earth's atmosphere strongly affects the properties of clouds and their impact on climate. Despite the importance of ice formation in determining the properties of clouds, the Intergovernmental Panel on Climate Change (IPCC, 2007) was unable to assess the impact of atmospheric ice formation in their most recent report because our basic knowledge is insufficient. Part of the problem is the paucity of quantitative information on the ability of various atmospheric aerosol spec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

53
1,459
4
10

Year Published

2014
2014
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 1,082 publications
(1,526 citation statements)
references
References 332 publications
(700 reference statements)
53
1,459
4
10
Order By: Relevance
“…The glaciation of these clouds is ascribed to heterogeneous ice nucleation occurring on the foreign surfaces of ice-nucleating particles (INPs) present in the cloud droplets. Ice nucleation induced by particles located within the body of water or aqueous droplets is termed immersion freezing and is probably the most important nucleation process turning liquid droplets in relatively warm clouds into ice crystals (Murray et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The glaciation of these clouds is ascribed to heterogeneous ice nucleation occurring on the foreign surfaces of ice-nucleating particles (INPs) present in the cloud droplets. Ice nucleation induced by particles located within the body of water or aqueous droplets is termed immersion freezing and is probably the most important nucleation process turning liquid droplets in relatively warm clouds into ice crystals (Murray et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…A number of field studies have demonstrated the dominant role of mineral dusts to nucleate ice in mixed phase clouds (Sassen et al, 2003;Ansmann et al, 2008;Pratt et al, 2009;Choi et al, 2010;Creamean et al, 2013) and possibly also in cirrus clouds (Cziczo et al, 2013). ATD is a commercial dust sample that has been used by many groups as a proxy of natural atmospheric mineral dust (Murray et al, 2012). It is a mixture of minerals with a considerable share of microcline, a K feldspar with a high ice nucleation ability as demonstrated in laboratory experiments (Atkinson et al, 2013;Zolles et al, 2015;Harrison et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, nucleation of water droplets and ice crystals in the atmosphere is a focus of a large body of research (Kärcher 2012;Murray et al 2012;Yakobi-Hancock et al 2013). Pure water droplets that contain no particulate matter do not form ice crystals at temperatures above −38°C.…”
Section: Introductionmentioning
confidence: 99%
“…3). Nominally, only one in a million particles can act as an INP at -20°C (39)(40)(41)(42)(43)(44)(45). If the temperature is reduced sufficiently, then all CCN can potentially act as sites for ice to form on by homogeneous freezing.…”
Section: Ice and Mixed-phase Cloudsmentioning
confidence: 99%